An annotated bibliography on Katherine Mansfield - Rodríguez Salas, Gerardo (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2004)
The present study complements Brownlee Jean Kirkpatrick’s bibliography on the New Zealand writer Katherine Mansfield, published in 1989. More than a decade has passed since its publication and criticism on Mansfield has increased substantially, creating the need to update Kirkpatrick’s material. This survey offers a careful selection of articles, book chapters, and monographic studies, also considering those published within the Spanish academic system. It starts by providing a list of the books and journals that include article collections on the writer, to make easier subsequent allusions.